Patients' and Family Members' Subjective Experiences of a Diagnostic Evaluation of Mild Cognitive Impairment. (February 2020) - Morris, Jonna L; Hu, Lu; Hunsaker, Amanda; Liptak, Amy; Seaman, Jennifer Burgher; Lingler, Jennifer H
Background: People with a diagnosis of mild cognitive impairment (MCI) often struggle with uncertainty and fear when learning of and coping with their diagnosis. However, little is known about their experiences and perspectives, and those of their care partners, when seeking out and undergoing a diagnostic evaluation for their cognitive symptoms. Method: This study is a secondary analysis of a focus group discussion that was initially conducted to learn the perspectives and experiences of participants and their care partners during a mock disclosure session of brain scan results. Participant's broader views on their experience of completing a cognitive evaluation resulting in an MCI diagnosis were evaluated in this study. Analysis used qualitative content methodology and line-by-line coding which generated categories and themes. Results: The (1) "presence of a threat" and (2) attempts to "minimize the threat" emerged as overarching themes driving the process of seeking out a diagnostic evaluation for cognitive symptoms. Subthemes that highlight the complexity of the presence of a threat included the "fear of stigma, " and the "emotional reactions" related to an MCI diagnosis. Three additional subthemes represented approaches that participants and their care partners used to minimize threat of MCI: "use of language" to minimize the threat; "information sharing and withholding"; and the "use of social support to legitimize personal experiences." Conclusion: These findings add to the literature by elucidating the uncertainty, fears, and coping strategies that accompany a diagnostic evaluation of MCI.